2018
DOI: 10.1371/journal.pone.0202446
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal methane emissions, metabolic, and microbial profile of Holstein steers fed forage and concentrate, separately or as a total mixed ration

Abstract: Few studies have examined the effects of feeding total mixed ration (TMR) versus roughage and concentrate separately (SF) on ruminant methane production. Therefore, this study compared differences in methane production, ruminal characteristics, total tract digestibility of nutrients, and rumen microbiome between the two feeding methods in Holstein steers. A total six Holstein steers of initial bodyweights 540 ± 34 kg were divided into two groups and assigned to a same experimental diet with two different feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 67 publications
8
45
4
1
Order By: Relevance
“…Furthermore, the PCoA plot and PCoA ellipses corresponding to the overall rumen microbiota of the two breeds were separated, indicating distinct different rumen microbiota harbored by each breed even fed the same TMR. Consistent with other studies (Bharanidharan et al, 2018;Difford et al, 2018;Xue et al, 2018), Prevotella had the most predominance in both breeds and at both sampling hours. Likewise, Pr.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the PCoA plot and PCoA ellipses corresponding to the overall rumen microbiota of the two breeds were separated, indicating distinct different rumen microbiota harbored by each breed even fed the same TMR. Consistent with other studies (Bharanidharan et al, 2018;Difford et al, 2018;Xue et al, 2018), Prevotella had the most predominance in both breeds and at both sampling hours. Likewise, Pr.…”
Section: Discussionsupporting
confidence: 91%
“…The average body weight (BW) was calculated as (the initial BW + the final BW)/2, and average daily gain (ADG) was recorded for the last 10 days of the experimental period. The TMR was sampled twice (at days 7 and 28) during the feeding trial, and the dry matter content was determined using a hot-air oven at 65°C for 72 h ( Bharanidharan et al, 2018 ). The chemical composition of the TMR was analyzed following the standard methods ( Aoac, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…The ratio of acetate, propionate, and butyrate generated in the rumen is affected by the type of forage and the species and quantity of rumen bacteria [5,6]. Meanwhile, sampling time is also an important factor affecting VFAs production [7].…”
Section: Introductionmentioning
confidence: 99%
“…TVFA: Total volatile fatty acid; 2 A/P: Acetate/ Propionate; 3 BF(0), before feeding (0 h); 4 AF(4), after feeding (4 h);5 SEM for feed × time;6 NS, not significant (p > 0.05); *, (p < 0.05); **, (p < 0.01).…”
mentioning
confidence: 99%
“…Similar findings have been previously reported by Bennink et al [ 34 ] who found 12.4% less CH 4 production with salt-induced elevated osmolality in the rumen of wethers. The earlier studies did not focus on the archaea community in relation to high osmolality, but feeding high-grain diets, which elevates ruminal osmolality [ 35 ], have been shown to reduce CH 4 production and formation [ 36 , 37 ], which favour the possible reduction or changes in archaea community structure. The current modifications in archaea diversity due to heat stress were too limited to affect the gas production parameters, which indicates that the metabolic role of archaea was relatively sustained unlike during osmotic stress conditions.…”
Section: Discussionmentioning
confidence: 99%